In-situ 3D observation of hydrogen-assisted particle damage behavior in 7075 Al alloy by synchrotron X-ray tomography. (1st April 2022) - Wang, Yafei; Toda, Hiroyuki; Xu, Yuantao; Shimizu, Kazuyuki; Hirayama, Kyosuke; Fujihara, Hiro; Takeuchi, Akihisa; Uesugi, Masayuki
Abstract: We directly captured, classified, and evaluated 3D particle debonding and fracture behavior in a H-charged 7075 Al alloy throughout the entire tensile deformation using synchrotron X-ray tomography and microstructural feature tracking techniques. The effects of particle size, shape, spatial clustering and stress state on strain-dependent particle damage were identified and isolated from each other. Moreover, state-of-the-art imaging and tracking techniques enabled the establishment of spatially and time-resolved hydrogen distributions during deformation. Based on realistic hydrogen partitioning among various nanoscopic trap sites, the contributions of particles to hydrogen trapping and the hydrogen effect at individual damaged particles were assessed quantitatively. Fracturing of coarse and irregular Al7 Cu2 Fe particles was found to be the predominant particle damage mode due to the spatial clustering and brittleness of these particles, but a hydrogen effect was not observed. The debonding of Mg2 Si particles seemed to be the result of competition between hydrogen and clustering-induced stress localization, but detrimental effects of hydrogen on ductile fracture induced by accelerating interfacial debonding were found to be limited. The quantitative evaluation of particle damage in the present model material clarified a viable strategy for mitigating hydrogen embrittlement, which involves introducing and modifying intermetallic particles with strong hydrogen trapping capacities. Graphical abstract: Image, graphical abstract